気道分泌の病態生理 - 安岡 劭 (The Journal of the Japan Society for Respiratory Endoscopy, 1984)
This work was carried out to clarify characteristics of bronchial secretion of normal subjects and patients with chronic bronchitis. (1) Experiment 1 Both bronchial lavage (BL) and bronchoalveolar lavage (BAL) were performed in young normal volunteers. And the biochemical components of BL and BAL fluid (secretion) were measured. Bronchial mucous glycoprotein content of the secretions was estimated by its fucose and sialic acid content. The biochemical component contents of the secretions were expressed according to the method of Stockley et al., to see degrees of local production of these components. The secretion-to-serum concentration ratios for albumin, IgG, IgA, lysozyme and sialic acid were calculated, and then the secretion-to-serum IgA, lysozyme and sialic acid ratios when standardised for the corresponding albumin ratio were 3, 430 and 2.5, respectively, even in the BAL fluid and significantly higher in the BL fluid than in the BAL fluid. In particular, the lysozyme ratio was about 5, 000 times that of albumin in the BL fluid. These results indicate that IgA and lysozyme, especially the latter in the bronchial region are locally secreted mainly from bronchial wall with mucus. The IgG ratio, however, was about 1-1.5 in both the BAL and BL fluid, suggesting that this immunoglobulin in the bronchoalveolar region of normal subjects is mainly derived from plasma. (2) Experiment 2 Mucoid sputa from patients with chronic bronchitis were centrifuged at 105, 000 xg for 1 hour, and the IgA, albumin, fucose and sialic acid contents of whole sputum and the supernatant were measured. The result indicated that about 80% of mucous glycoprotein and 50-60% of albumin, IgA and lysozyme were distributed in the precipitate (gel phase). The fucose, sialic acid, IgA, lysozyme and albumin concentration in the 105, 000 xg supernatant were significantly correlated with each in the whole sputum. The secretion-to-serum IgA, lysozyme and sialic acid ratios standardised for the corresponding albumin ratio were similar in the BL fluid of normal subjects and the 105, 000 xg supernatant from mucoid sputum of patients with chronic bronchitis, suggesting that secretion of mucus and proteins by bronchial mucous and serous glands are proportionally increased with release of immunoglobulin by lymphocytes and probably with transudation of proteins from blood, in bronchial region of patients with chronic bronchitis. (3) Experiment 3 It was shown that by gel filtration of the supernatant from sputum on Sepharose 4B that both fucose and sialic acid in sputum exist in free form besides as constituents of mucous glycoprotein, and amounts of free fucose and sialic acid vary from sputum to sputum. Therefore it is postulated that fucose and sialic acid contents of whole sputum do not always reflect its mucous glycoprotein content. 気道分泌液, 正確には気道液は気道壁の分泌細胞とリンパ球, 血液, 肺胞被覆層と起源を異にする水分, 電解質, 粘液糖蛋白, 蛋白, 脂質等の諸成分から構成されており, 全体として粘弾性を示す。気道液は本来気道, 呼吸器疾患の発症や進展を防ぐ役割を果しており, 粘液一線毛運動はその代表的機序である。気道疾患が成立すると, 種々の機序により一般に気道分泌が亢進し, 気道液の量の増加と質的変動が起こり, 喀痰, 咳, 呼吸困難などの臨床症状の原因になる。気道疾患の発症防止法やその治療法の開発のためには, 正常時と病態時の気道液の差違, 気道液の生物学的ならびに物理学的特性などの問題が物のレベルで, すなわち生化学的に解明される必要がある。ここでは, 気道一肺胞洗浄法による気道-肺胞系の各レベルによる生体防御成分の差違の追求と, 慢性気管支炎における気道液の変動の機序や喀痰の物理学的特性の背景となる構造上の特徴などを追求するうえでの問題点を述べた。